Paravertebral block for management of acute postoperative pain and intercostobrachial neuralgia in major breast surgery - Gacio,Mercedes Fernández (2016)
Abstract Background: Several locoregional techniques have been described for the management of acute and chronic pain after breast surgery. The optimal technique should be easy to perform, reproducible, with little discomfort to the patient, little complications, allowing good control of acute pain and a decreased incidence of chronic pain, namely intercostobrachial neuralgia for being the most frequent entity. Objectives: The aim of this study was to evaluate the paravertebral block with preoperative single needle prick for major breast surgery and assess initially the control of postoperative nausea and vomiting (PONV) and acute pain in the first 24 h and secondly the incidence of neuropathic pain in the intercostobrachial nerve region six months after surgery. Methods: The study included 80 female patients, ASA I-II, aged 18-70 years, undergoing major breast surgery, under general anesthesia, stratified into 2 groups: general anesthesia (inhalation anesthesia with opioids, according to hemodynamic response) and paravertebral (paravertebral block with single needle prick in T4 with 0.5% ropivacaine + adrenaline 3 µg mL−1 with a volume of 0.3 mL kg−1 preoperatively and subsequent induction and maintenance with general inhalational anesthesia). In the early postoperative period, patient-controlled analgesia (PCA) was placed with morphine set for bolus on demand for 24 h. Intraoperative fentanyl, postoperative morphine consumption, technique-related complications, pain at rest and during movement were recorded at 0 h, 1 h, 6 h and 24 h, as well as episodes of PONV. All variables identified as factors contributing to pain chronicity age, type of surgery, anxiety according to the Hospital Anxiety and Depression Scale (HADS), preoperative pain, monitoring at home; body mass index (BMI) and adjuvant chemotherapy/radiation therapy were analyzed, checking the homogeneity of the samples. Six months after surgery, the incidence of neuropathic pain in the intercostobrachial nerve was assessed using the DN4 scale. Results: The Visual Analog Scale (VAS) values of paravertebral group at rest were lower throughout the 24 h of study 0 h 1.90 (±2.59) versus 0.88 (±1.5) 1 h 2.23 (±2.2) versus 1.53 (±1.8) 6 h 1.15 (±1.3) versus 0.35 (±0.8); 24 h 0.55 (±0.9) versus 0.25 (±0.8) with statistical significance at 0 h and 6 h. Regarding movement, paravertebral group had VAS values lower and statistically significant in all four time points: 0 h 2.95 (±3.1) versus 1.55 (±2.1); 1 h 3.90 (±2.7) versus 2.43 (±1.9) 6 h 2.75 (±2.2) versus 1.68 (±1.5); 24 h 2.43 (±2.4) versus 1.00 (±1.4). The paravertebral group consumed less postoperative fentanyl (2.38 ± 0.81 µg kg−1 versus 3.51 ± 0.81 µg kg−1) and morphine (3.5 mg ± 3.4 versus 7 mg ± 6.4) with statistically significant difference. Chronic pain evaluation of at 6 months of paravertebral group found fewer cases of neuropathic pain in the intercostobrachial nerve region (3 cases versus 7 cases), although not statistically significant. Conclusions: Single-injection paravertebral block allows proper control of acute pain with less intraoperative and postoperative consumption of opioids but apparently it cannot prevent pain chronicity. Further studies are needed to clarify the role of paravertebral block in pain chronicity in major breast surgery.